Digital Narrator as a Game Master. The Case of Baldur’s Gate III - Nawrocki, Maciej (Transfer. Reception Studies, 2024)
This article is a preliminary exploratory analysis of the narrator in Baldur’s Gate III seen as a digital simulation of an analogue game master (GM). As the reception of Baldur’s Gate series has always been closely linked to its analogue predecessor, Dungeons & Dragons, the main context of the analysis is theoretical reflections concerning tabletop role-playing games (TRPG), especially in relation to digital ones. The analysis covers not only a close reading of some of the in-game utterances, but also the commentary of Amelia Tyler, the actress lending her voice to the narrator. The author argues that while all installments of the series attempted to re-create certain experiences characteristic of TRPG sessions through the digital medium, one of key differences between Baldur’s Gate III and its predecessors is that it features a complex, voiced narration, designed according to real-life GMs.